Conditions of Invertibility for Functional Operators with Shift in Weighted Hölder Spaces - Karelin, O.; Tarasenko, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We consider functional operators with shift in weighted Hölder spaces. The main result of the work is the proof of the conditions of invertibility for these operators. We also indicate the forms of the inverse operators. As an application, we propose to use these results for the solution of equations with shift encountered in the study of cyclic models for natural systems with renewable resources.